'To more than I can be': A phenomenological meta-ethnography of singing groups for people with chronic obstructive pulmonary disease. (September 2021) - Yoeli, Heather; Macnaughton, Jane
Anecdotal experience and qualitative accounts suggest that singing groups, classes or choirs specifically for people with COPD (henceforth referred to as COPD-SGs) are effective in improving health. However, this is not reflected in the quantitative evidence. This meta-ethnography deployed phenomenological methods to explore this discrepancy. Analysis identified the phenomena of being together, being uplifted and being involved as central benefits of COPD-SGs. When viewed through the phenomenological lens of body-social as distinct from body-subject and body-object, findings demonstrated that the qualitative effectiveness of COPD-SGs is greatest on a collective basis. Qualitative research into the effectiveness of COPD-SGs offers more favourable results because phenomenological approaches can identify collective benefits that quantitative methods cannot. COPD-SGs should seek to maximise these collective benefits by rediscovering their cultural and artistic heritage within the national and global Arts in Health (AiH) movement, which has long emphasised the radical creative and healing power of group activity.